Correlation Among Self-Care Ability, Psychological Status, and Quality of Life in Discharged Patients with Hepatolithiasis Complicated with Diabetes Mellitus and T-Tube - Huang, Chunqiu; Wang, Ying; Cai, Yimin; Shen, Zhoumin; Zhang, Honghui; Tan, Zhaoxia; Chen, Hongjiao; Zhou, Bifang (Frontiers in Surgery, 2022)
Objective To investigate the correlation between self-care ability, psychological status and quality of life in patients with hepatolithiasis complicated with diabetes mellitus with T tube. Methods The purpose of this study was to select a total of 240 patients with hepatolithiasis complicated with diabetes with T tube from June to September, 2019 in a Third-class Grade A hospital in Changsha, Hunan Province. Self-designed general information questionnaire, Self-care ability implementation scale (ESCA), Self-rating Anxiety Scale (SAS), Self-rating Depression Scale (SDS), and quality of life scale (SF-36) were used to conduct a questionnaire survey. The correlation among self-care ability, psychological status and quality of life of patients with hepatolithiasis complicated with diabetes mellitus with T tube was analyzed. Results The total score of self-care ability of 240 patients with hepatolithiasis combined with diabetes with T tube was positively correlated with the total score of quality of life (P<0.05). The standard scores of anxiety and depression were negatively correlated with the total score of quality of life (P < 0.05). The total score of self-care ability was negatively correlated with the standard score of anxiety and depression (P < 0.05). Conclusion Improving the self-care ability of patients with hepatolithiasis complicated with diabetes with T tube and improving their anxiety and depression can improve their quality of life，which provide reference for further study.